PENGARUH KETERAMPILAN LITERASI TERHADAP PENGGUNAAN BAHASA PADA PENULISAN KATA BAKU DAN TIDAK BAKU - Julyanti Fransisca; Ahmad Nurefendi Fradana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research is motivated by errors that are often experienced in examples of Indonesian, one of which is errors in language use in writing standard and non-standard words due to students' lack of reading interest in reading the KBBI (Big Indonesian Dictionary). This research aims to determine the effect of literacy on language use in writing standard and non-standard words with the help of Handout learning media. The research technique used in this research is the experimental method. The experimental research design used is a pre-experimental design with a One-Group Pretest-Posttest design type, a type of research that provides a pretest design before a treatment is given. The research was carried out at SDN Lemahputro 1 in class 6 using curriculum 13. Data analysis using the paired sample T-test using SPSS version 24 obtained a Sig. (2-tailed) 0.000 < 0.05 then Ho is rejected and Ha is accepted. The average before treatment was 56.67 and after treatment was 82.22. It can be concluded that there is an influence on literacy on language use in writing standard and non-standard words to increase language use in writing standard and non-standard words.